Trade rules in e-commerce: WTO and India - Arpita Mukherjee; Avantika Kapoor (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Electronic commerce (e-commerce) is an integral part of business activities, and various models of e-commerce have emerged with liberalisation and technological developments. Global e-commerce trade has seen fast growth, which is predicted to continue in the future. The sector is now discussed in various international forums, and a group of countries are exploring the possibility of open, transparent and non-discriminatory e-commerce trade rules in the WTO. India has not joined this group as commitments in the WTO may reduce the ability of the government to promote and support domestic industry. India is also actively engaged in bilateral and regional trade agreements such as the Regional Comprehensive Economic Partnership (RCEP), and e-commerce is a key component of such agreements. Given this background, the objective of this paper is to understand the growth of the e-commerce sector globally and in India, the developments in the WTO, and India's position. Based on secondary data and information, and one-on-one meetings with 30 stakeholders, the paper makes policy recommendations on what India's strategy in the WTO should be. The study found that India does not have data on trade in e-commerce, which can help identify the country's strengths and areas of concerns, based on which policymakers can take informed decisions. The regulatory regime for e-commerce is evolving across the world and India is no exception. While the study has identified certain gaps and inconsistencies in the regulations, the autonomous regime in India is more liberal than that implemented by countries which are willing to negotiate trade rules. The paper recommends that India should join the negotiations. Simultaneously, it needs to collect data and information on (a) different business models, (b) issues faced by e-commerce companies in scaling up, (c) how e-commerce can be used as a platform to promote exports of handicraft, apparel and other products, and (d) what needs to be done to make India a global manufacturing and sourcing hub. India should support its domestic industry and domestic e-commerce players. However, such support should be given in a way that is consistent with the country's commitments to the WTO and helps e-commerce companies scale up at a fast pace. India may also review regulations implemented by other countries on issues such as data protection and consumer privacy, and design its own regulations based on global best practices and the country's requirements. It can also collaborate with like-minded countries to develop strategies to protect domestic policy space. A defensive position in the WTO may force India to accept trade rules in e-commerce in the future that may not benefit the country.
Keywords: F13; F42; F53; L81; 330; e-commerce; WTO; trade; India; FTA